The origin of the "dark" absorption band near 675 nm in the purple bacterial core light-harvesting complex LH1: two-photon measurements of LH1 and its subunit B820 - Razjivin, Andrei; Solov'ev, Alexander; Kompanets, Victor; Chekalin, Sergey; Moskalenko, Andrey; Lokstein, Heiko (Photosynthesis research, 2019)
A comparative two-photon excitation spectroscopic study of the exciton structure of the core antenna complex (LH1) and its subunit B820 was carried out. LH1 and its subunit B820 were isolated from cells of the carotenoid-less mutant G9 of Rhodospirillum rubrum. The measurements were performed by two-photon pump-probe spectroscopy. Samples were excited by 70 fs pulses at 1390 nm at a frequency of 1 kHz. Photoinduced absorption changes were recorded in the spectral range from 780 to 1020 nm for time delays of the probe pulse relative to the pump pulse in the - 1.5 to 11 ps range. All measurements were performed at room temperature. Two-photon excitation caused bleaching of exciton bands (k = 0, k = ± 1) of the circular bacteriochlorophyll aggregate of LH1. In the case of the B820 subunit, two-photon excitation did not cause absorption changes in this spectral range. It is proposed that in LH1 upper exciton branch states are mixed with charge-transfer (CT) states. In B820 such mixing is absent, precluding two-photon excitation in this spectral region. Usually, CT states are optically "dark", i.e., one photon-excitation forbidden. Thus, their investigation is rather complicated by conventional spectroscopic methods. Thus, our study provides a novel approach to investigate CT states and their interaction(s) with other excited states in photosynthetic light-harvesting complexes and other molecular aggregates.
Keywords: Rhodospirillum rubrum; Photosynthesis; Spectrum Analysis; Photons; bakteriochlorofyly; Light-Harvesting Protein Complexes; světlosběrné proteinové komplexy; Carotenoids; Bacteriochlorophylls; fotosyntéza; spektrální analýza; fotony; karotenoidy